Characterization and immunogenicity assessment of MERS-CoV pre-fusion spike trimeric oligomers as vaccine immunogen - Rahul Ahuja; Preeti Vishwakarma; Sneha Raj; Varun Kumar; Ritika Khatri; Bharat Lohiya; Shikha Saxena; Gurleen Kaur; Gagandeep Singh; Shailendra Asthana; Shubbir Ahmed; Sweety Samal (Taylor & Francis Group, 2024)
ABSTRACTMiddle East respiratory syndrome coronavirus (MERS-CoV) is a lethal beta-coronavirus that emerged in 2012. The virus is part of the WHO blueprint priority list with a concerning fatality rate of 35%. Scientific efforts are ongoing for the development of vaccines, anti-viral and biotherapeutics, which are majorly directed toward the structural spike protein. However, the ongoing effort is challenging due to conformational instability of the spike protein and the evasion strategy posed by the MERS-CoV. In this study, we have expressed and purified the MERS-CoV pre-fusion spike protein in the Expi293F mammalian expression system. The purified protein was extensively characterized for its biochemical and biophysical properties. Thermal stability analysis showed a melting temperature of 58°C and the protein resisted major structural changes at elevated temperature as revealed by fluorescence spectroscopy and circular dichroism. Immunological assessment of the MERS-CoV spike immunogen in BALB/c mice with AddaVaxTM and Imject alum adjuvants showed elicitation of high titer antibody responses but a more balanced Th1/Th2 response with AddaVaxTM squalene like adjuvant. Together, our results suggest the formation of higher-order trimeric pre-fusion MERS-CoV spike proteins, which were able to induce robust immune responses. The comprehensive characterization of MERS-CoV spike protein warrants a better understanding of MERS spike protein and future vaccine development efforts.